Implementation of Stunting Prevention Policies in Bogor City - Shabrina, Heldiani Nur; Putri, Fitrianindita Rahayu; Saputro, Yudha Dwi; Rafisyah, Achmad Zaidan; Rahman, Abdul (Jurnal Pemerintahan dan Kebijakan (JPK), 2025)
This research aims to analyze stunting prevention policies in Bogor City using the theoretical framework of George Edward III's policy implementation model. The method employed was a literature review with a qualitative approach, referring to secondary data from journals, policy documents, and other literature sources. The findings showed that stunting prevention policies in Bogor City have been implemented through several programs, such as Penting Lur, SALSA, Taleus, and the Program Keluarga Harapan (PKH), with varying levels of effectiveness. Communication factors, resources, disposition, and bureaucratic structure play an important role in determining the success of policy implementation. However, challenges such as cross-sectoral coordination, limited resources in certain areas, and low public awareness of nutrition remain obstacles that must be addressed. The findings are expected to serve as a reference for policymakers in improving the effectiveness of stunting prevention programs locally, particularly in Bogor City.